Thailand : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the IMF's projections and estimates on Thailand's expenditure on gross domestic product at current prices; balance of payments during 1995-2000; gross domestic product by industrial origin at current and constant prices during 1995-99; investment and savings at constant prices; gross domestic product at 1988 prices; selected energy prices; mining and agricultural productions during 1995-2001; central government fiscal accounts and revenue and grants; central government expenditure by economic classification,1995/96-1999/2000; summary of the central and local government tax system; financial and monetary surveys during 1996-2001, and so on.